A Study to Assess the Effectiveness of Home-based Stretching Exercises on Joint Pain Among Clients with Osteoarthritis in Selected Old Age Home, Rajkot City, Gujarat - Naman Vyas (International Journal of Orthopedic Nursing and Practices, 2023)
Osteoarthritis (OA) is a commonly encountered condition in middle-aged and older individuals, marked by its slow development. Strengthening exercises targeting the quadriceps muscles, situated in the front thigh, can mitigate knee pain, and reduce disability associated with OA. The musculoskeletal system encompasses the bones of the skeleton, the joints where these bones connect, and the muscles responsible for enabling and regulating movement. The knee, the largest and most complex joint, bears the body’s weight, supports upright posture, acts as a hinge for walking, and endures considerable stresses during physical activities like running and sports. OA, known as degenerative joint disease, is a persistent ailment marked by the slow deterioration of the cartilage found in joints. It commonly affects weight-bearing joints such as hips, knees, and finger joints, leading to symptoms like joint pain, stiffness, swelling, audible cracking during movement, and diminished joint function. Globally prevalent, OA significantly impacts functionality and diminishes life quality. Clinically, it presents joint pain, stiffness, restricted movement, occasional swelling, and varying degrees of localized inflammation. Pain in OA stems from structural changes and peripheral and central pain processing, affecting physical abilities. OA-induced changes can restrict mobility, hinder daily activities, personal care, work performance, and household management. Joints are typically composed of hyaline cartilage, pivotal for joint functionality during bodily movements. This cartilage primarily consists of collagen type II and aggrecan proteoglycan, contributing to its viscoelastic and compressive properties. Osteoarthritis, characterized by articular cartilage degeneration without inflammation, affects weight-bearing joints like hips, knees, and finger interphalangeal joints. Symptoms include joint pain, stiffness, swelling, cracking noises during movement, and reduced joint function.
Keywords: Osteoarthritis; joint function; knee pain; musculoskeletal system; peripheral and central pain processing